Immunization knowledge and practice among Malaysian parents: a questionnaire development and pilot-testing - Awadh, Ammar Ihsan JawaD; Hassali, Mohamed Azmi; Al-lela, Omer Qutaiba; Elkalmi, Ramadan Mohamed Mahmod; Bux, Siti Halimah; Ab. Hadi, Hazrina (BioMed Central, 2014)
Parents are the main decision makers for their children vaccinations. This fact makes parents’ immunization knowledge and practices as predictor factors for immunization uptake and timeliness. The aim of this pilot study was to develop a reliable and valid instrument in Malaysian language to measure immunization knowledge and practice (KP) of Malaysian parents.